Asymptotic performance analysis of untrusted relay system with full-duplex jamming destination - Rui ZHAO; Xing TAN; Yuanjian LI; Yucheng HE; Chunguo LI (Tongxin xuebao)
The cooperative relay technique in the field of physical layer security is widely concerned by the academic community,due to the advantages of increasing the network capacity and expanding the network coverage.However,cooperative relays may play as untrusted nodes in some certain circumstances.Based on this,to enhance the secrecy performance of untrusted relay systems,a novel full-duplex destination jamming (FDJ) scheme was proposed in the Rayleigh fading channel.In order to maximize the system’s secrecy capacity,a switchable split-optimal antenna selection (OAS) scheme was proposed for a multiple-antenna destination,the power allocation optimization scheme between the source and destination was designed,and the corresponding closed-form expressions of secrecy performance were given.In the large-scale antennas analysis,the closed-form expressions of the ergodic achievable secrecy rate and the optimal power allocation factor of instantaneous secrecy capacity for the FDJ-OAS scheme were derived.Furthermore,based on different asymptotic cases,the asymptotic analyses of secrecy outage probability for the FDJ-OAS scheme were significantly analyzed.Simulation results show that the analytical curves match well with the Monte-Carlo simulation results.It is concluded that the diversity order of the FDJ-OAS scheme is proportional to the number of antennas and antenna diversity can be achieved,which reveals the advantages of the proposed FDJ-OAS scheme.